2020
DOI: 10.1039/d0tc01856b
|View full text |Cite
|
Sign up to set email alerts
|

Doping of silicon by phosphorus end-terminated polymers: drive-in and activation of dopants

Abstract: An effective doping technology for precise control of P atom injection and activation into a semiconductor substrate is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…‰, Figure C2). Our method offers the same information as for dopant distributions that have been studied for bulk materials, for example, n-type semiconductors. We further confirmed these results with the good agreement of those obtained from XPS by comparing the estimated penetration-depth to the inelastic mean-free path information depth (error <5%, Figure S7 and Table S3). …”
Section: Resultssupporting
confidence: 75%
“…‰, Figure C2). Our method offers the same information as for dopant distributions that have been studied for bulk materials, for example, n-type semiconductors. We further confirmed these results with the good agreement of those obtained from XPS by comparing the estimated penetration-depth to the inelastic mean-free path information depth (error <5%, Figure S7 and Table S3). …”
Section: Resultssupporting
confidence: 75%
“…From the point of view of the target application, these data highlight that, even taking into account all these phenomena, the proposed approach guarantees a high level of control on the dopant concentration in the δ-layer. In previous papers, Perego et al showed excellent control of the doping level in silicon substrates by means of thermal diffusion of P atoms from dopant sources created via grafting of phosphorus end-terminated polymers. ,, The proposed doping approach relies on the main assumption that, taking advantage of the self-limiting nature of the “grafting to” process from the melt, proper selection of the polymer M n guarantees precise control of the areal dose and spatial distribution of dopants. Present work indicates that the effective grafting density of the polymer chains onto the Si substrate is not fully controlled by the selection of the M n , but it is somehow affected by the polydispersity of the phosphorus end-terminated polymers that are used to create the brush layer.…”
Section: Discussionmentioning
confidence: 99%
“…A cumulative and stepwise increase in the dose of P atoms grafted to the silicon surface is demonstrated by simple iteration of grafting/ashing cycles. 27,29,30 Upon deposition of a SiO 2 layer to prevent P outgassing, P atoms were efficiently injected into the Si substrate by high-temperature thermal treatments, demonstrating high activation rates (80%) of injected P atoms. 29 From this point of view, the proposed doping technology present several advantages compared to other polymer-assisted doping approaches that have been proposed by other groups in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] In addition to sub-10 nm junction depth, tailorable molecular structures of the polymer enable access to tens-of-nanometer patterning by leveraging self-assembly instead of photolithography. [13,14] Current efforts have been devoted to extending polymeric doping to a variety of molecular architectures, including dendrimers, [15,16] brushes, [17][18][19] and micelles. [9] While the dendrimer and brush approaches have demonstrated control of the dose by changing molecular weight, spatial patterning is limited to a micrometer length scale.…”
Section: Introductionmentioning
confidence: 99%